2006
DOI: 10.1381/096089206775565131
|View full text |Cite
|
Sign up to set email alerts
|

Detachment of the Connecting Tube from the Port and Migration into Jejunal Wall

Abstract: After laparoscopic adjustable gastric banding (LAGB), early recognition and treatment of uncommon complications are important. A 36-year-old man who had undergone LAGB presented at our clinic with weight gain of 14 kg during the prior 6 months. During investigation, detachment of the connecting tube from the port and migration of this tube into the jejunal wall were found. The detached port was replaced with a new port, and laparoscopically-assisted jejunorraphy was performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 4 publications
0
25
0
Order By: Relevance
“…It was treated by laparotomy and ileal resection with removal of the connecting tubing. Zengin et al [13] reported a case of disconnection of the tubing from the subcutaneous port with subsequent erosion into the jejunal wall in a 36-year-old man post LAGB. Hartmann et al [14] reported colonic perforation by the connecting tube.…”
Section: Discussionmentioning
confidence: 99%
“…It was treated by laparotomy and ileal resection with removal of the connecting tubing. Zengin et al [13] reported a case of disconnection of the tubing from the subcutaneous port with subsequent erosion into the jejunal wall in a 36-year-old man post LAGB. Hartmann et al [14] reported colonic perforation by the connecting tube.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these patients underwent investigation for pelvic inflammatory disease, gynecological problems, renal colic, or acute appendicitis. Small-bowel obstruction and migration into jejunal and colonic walls caused by the connecting tube were reported in patients with prolonged abdominal pain [8][9][10][11]. Ability for free food passage and weight gain are other clinical signs of tube disconnection.…”
Section: Discussionmentioning
confidence: 99%
“…Additional investigations including abdominal plain film, injection of contrast dye through the port, scintigraphy, or abdominal computed tomography (CT) scan can be performed to confirm diagnosis of tube detachment [8,10,11]. In our opinion this is unnecessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Major post-operative complications are uncommon but their occurrence has to be followed by a prompt diagnosis and proper treatment [2][3][4][5][6][7]. These complications can be related either to the port or the connecting tube, such as infection, tube disconnection or dislocation, or to the band, such as band slippage, pouch dilatation, and band erosion [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%